Pengembangan Alat Peraga Bak Simulasi Riak Gelombang pada Materi Gelombang untuk Peserta Didik SMA/MA - Riska Putri; Rahma Diani; Yuberti Yuberti (Pendidikan Fisika Universitas Nurul Huda, 2020)
This research aims to develop physics learning media in the form of ripple tank on wave subject. One of the problems in education is the lack of facilities and infrastructure, so teachers are required to be creative in improving learning quality in the classroom, such as making props as one of the learning media. One of the interesting learning media that can overcome students’ boredom in learning is through props-making based learning. The method used in this study is research and development. The type of research used is the 4D model. The data in this study were collected in the form of a questionnaire given to content experts, media experts, teachers and 10th-grade students. The type of data generated is qualitative and quantitative data to determine the accuracy of the products, so that, it can produce physics learning media in the form of props that is valid for use based on the assessment of the content expert validator and the media expert validator with very accurate categories, and based on the assessment from teachers and students got scores with very interesting categories. This shows that the product developed can be used in learning to facilitate students in understanding wave subject.